Who's the Boss? Concepts of Social Power Across Development. Issue 3 (14th October 2016) - Gülgöz, Selin; Gelman, Susan A.
Abstract : Power differences are observed in children's early relationships, yet little is known about how children conceptualize social power. Study 1 recruited adults ( n = 35) to assess the validity of a series of vignettes to measure five dimensions of social power. Using these vignettes, Study 2 (149 three‐ to nine‐year‐olds, 42 adults) and Study 3 (86 three‐ to nine‐year‐olds, 22 adults) showed that children visiting a science museum at a middle class university town are sensitive to several dimensions of social power from a young age; however, an adult‐like breadth of power concepts does not develop until 7–9 years. Children understand social power whether the powerful character is malevolent or benevolent, though malevolent power is easier to detect for children and adults.